Transarterial Chemoembolization Combined With Apatinib for Advanced Hepatocellular Carcinoma: A Propensity Score Matching Analysis - Kan, Xuefeng; Liang, Bin; Zhou, Guofeng; Xiong, Bin; Pan, Feng; Ren, Yanqiao; Cao, Yanyan; Wang, Jihua; Yang, Fan; Zheng, Chuansheng (Frontiers in Oncology, 2020)
Background: Apatinib is a powerful inhibitor of vascular endothelial growth factor receptor-2. This study was aimed to investigate whether apatinib could improve the efficacy of transarterial chemoembolization (TACE) in patients with advanced hepatocellular carcinoma (HCC). Methods: Between June 2015 and September 2018, 357 patients with HCC at Barcelona Clinic Liver Cancer stage C who received the treatment of TACE combining with apatinib (TACE–apatinib) or TACE-alone were included. Propensity score matching (PSM) analysis was used to reduce the patient selection bias. Results: Ninety pairs of patients were chosen after the PSM analysis. The disease control rates of tumor and a-fetoprotein response in the TACE–apatinib group were significantly higher than that of the TACE-alone group before and after the PSM analysis (P < 0.05). Before the PSM analysis, the median time of tumor progression (TTP) and the overall survival (OS) in the TACE–apatinib group were significantly greater than those of the TACE-alone group (TTP: 9.0 months vs. 3.0 months, P < 0.001; OS: 14.0 months vs. 7.0 months, P < 0.001). After the PSM analysis, the median TTP and OS in the TACE–apatinib group was also significantly greater than that of the TACE-alone group (TTP: 7.0 months vs. 3.0 months, P < 0.001; OS: 13.0 months vs. 8.0 months, P < 0.001); the uni- and multivariate analysis revealed that TACE–apatinib was a protective factor for OS. Fourteen patients emerged with grade 3 apatinib-related adverse events. Conclusion: The efficacy of TACE–apatinib for patients with advanced HCC was inspiring, and the side effects of apatinib were tolerable.